Comparison Between Cold Dissection and Bipolar Electro Cautery Techniques in Tonsillectomy at Sarwari Hospital - Shah , Ghafoor; Sabirzai, Mohammad Kamil (International Journal For Research In Health Sciences And Nursing, 2021)
Introduction: Tonsillectomy is one of the most common surgeries in the head and neck world-wide. This operation is carried out by different methods, the most frequent of which are the cold dissection and bipolar electro cautery techniques. Objective: This study was conducted to assess and compare postoperative morbidity between cold dissection and bipolar electro cautery. Methods: This study was performed on 86 patients who under-went tonsillectomy in Sarwari Hospital from 22nd, June, 2019 to 23rd December, 2019. They divided in to two groups by lottery method, Group A (43 patients) which was done Bipolar Electro cautery (Valleylab Electrocauery model 2010) technique and group B (43 patients) which was done Cold dissection (Instruments like Boyle Davis mouth gag, Tonsillar scissor, Dissector, pillar retractor, tonsillar snare and ligator ). Time of surgery, amount of intraoperative blood loss, postoperative haemorrhage, the intensity of local pain 4 and 24 h after operation and nausea and/or vomiting were recorded and compared in the two groups to decide which technique is better. The data were analysed in SPSS software (ver-22). The p-value less than 0.05 was considered significant. Results: This prospective randomized controlled clinical trial was performed on 86 patients who under-went tonsillectomy in Sarwari Hospital from 22nd, June, 2019 to 23rd December, 2019. 49 (56.97%) of them were male and 37 (43.03%)of them were female patients and they divided in to two groups by lottery method, Group A (43 patients) which was done Bipolar Electro cautery technique and group B (43 patients) which was done Cold dissection In this study, the average intraoperative blood loss was significantly lower (p < 0.05) in the bipolar electro-cautery technique group, while the intensity of local pain 4 and 24 h after the operation was significantly higher (p < 0.05). Other variables showed no significant differences between the two groups. Conclusion: Based on the findings of the present investigation, the bipolar electro cautery technique is suggested for tonsillectomy in children, while the cold dissection technique is preferred for adult patients